The Role of Financial Performance as Intellectual Capital Mediation Variable on Company Value in Pharmaceutical Sub Sector Companies - Retno Paryati (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of intellectual capital on firm value in the pharmaceutical sub-sector listed on the Stock Exchange with financial performance as an intervening variable. The independent variable used in this study is intellectual capital as measured by the value added intellectual coefficient (VAIC). The dependent variable in this study is firm value measured using price to book value (PBV), while financial performance as an intervening variable is measured using return on assets (ROA). The sample used in this study were 8 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 period. This study uses a quantitative approach with hypothesis testing using simple linear regression analysis methods, multiple linear regression analysis. To test the effect of mediation, the Sobel test was used. The results showed that (1) intellectual capital had no significant effect on financial performance. (2) intellectual capital has a significant effect on the level of firm value. (3) financial performance has no significant effect on the level of firm value. (4) Sobel test results show that financial performance cannot mediate intellectual capital on firm value.